Factors associated with suicidal ideation and suicidal behaviors: a review of studies on adolescents and youth in Latin America - Corrales Felipe, Hugo Alfredo (2021)
The present work aimed to identify the factors associated with suicidal ideation and behaviors in populations of adolescents and young people in Latin America, under a systematic review, eight articles were analyzed through which four factors were identified as the most outstanding, What are they; the low perception of social support, the activities carried out in free time, the experiences of violence and personal resources. When these are permanent, they become risk factors, by identifying these factors it was possible to have an overview of those associated with suicide and at the same time it is possible to intervene and establish preventive actions.